Sobre dos posibles topónimos en un plomo ibérico del Camp de Morvedre (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper tries to show the posible relationship between the iberian words arsboiltiĚ and etem²iltiĚ, in a lead found in the Camp de  Morvedre, and the place-names Arse (Sagunto) and Edeta (Cerro de Sant Miquel de Llíria), respectively.